A salt spray resistant two-component epoxy zinc-rich primer and preparation method thereof
By using nanomaterials and bentonite montmorillonite in epoxy zinc-rich primer, the problems of thermal exothermic, large porosity and low safety of existing epoxy zinc-rich primer are solved, and its adhesion is improved and salt spray resistance, achieving better corrosion resistance.
Patent Information
- Application Number
- CN202310336090.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-03-31
AI Technical Summary
The existing epoxy zinc-rich primer has problems such as heat exothermic, large porosity, cracking, high raw material cost and low safety during the film formation process. The consumption of zinc powder leads to an increase in osmotic pressure, which limits its long-term Anti-corrosion performance.
Using two-component epoxy zinc-rich primer, the use of nano-inorganic phosphate, polypyrrole nanosheets, zinc powder, iron phosphate powder and aluminum tripolyphosphate, combined with lithium-based bentonite and lithium-based montmorillonite as anti-settlement Reagents and thickeners reduce the amount of zinc powder, enhance the density of the coating and corrosion resistance.
It improves the adhesion and salt spray resistance of the primer, reduces the amount of zinc powder, avoids coating cracking, enhances mechanical properties and chemical stability, and improves corrosion resistance.
Smart Images

Figure CN116396661B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and particularly relates to a salt-spray resistant two-component epoxy zinc-rich primer and a preparation method thereof. Background Art
[0002] Cyclic zinc-rich primer is a special coating mainly used in marine engineering, ships, bridges, metallurgy, electric power, petrochemical and other fields. It usually uses epoxy resin as a film-forming substance and amine or modified amine adduct as a curing agent, adds ultra-fine zinc powder, additives and solvents, and is coated on the surface of the steel substrate to act as a sacrificial anode to protect the cathode steel substrate from corrosion. Because zinc is more active than iron, when the electrochemical reduction-oxidation reaction occurs, Zn loses electrons in the anode area and becomes Zn 2+ ions, zinc powder is consumed and corroded, and in the cathode area, divalent Fe 2+ The electrons are reduced to Fe, and the cathode is protected from corrosion.
[0003] Since epoxy zinc-rich primer contains a large amount of zinc powder, there are the following disadvantages: (1) Heat is released during the film formation process, and cooling equipment is required to maintain the stability of the epoxy zinc-rich primer system, which increases the cost of production equipment; (2) After the film is formed, there are many pores, and when the film thickness of the one-time coating is too large, it is easy to crack; (3) Zinc powder is expensive, relatively active, and has low safety. During use, the cost of raw materials will increase and there will be inevitable safety problems; (4) During the primer application process, a large amount of water-soluble Zn is generated along with the consumption of zinc powder. 2+ , which will lead to an increase in osmotic pressure, which is very likely to cause rust and blistering of the substrate, so its long-term anti-corrosion protection is limited. Summary of the invention
[0004] The invention aims to provide a salt spray resistant two-component epoxy zinc-rich primer, which has outstanding adhesion and excellent salt spray resistance.
[0005] The technical solution adopted by the present invention to solve the above-mentioned problem is: a salt spray resistant two-component epoxy zinc-rich primer, comprising component A and component B in a weight ratio of (15-20): (1-1.5);
[0006] The weight proportions of the raw materials in the A component are as follows: 7-10 parts of liquid epoxy resin, 10-15 parts of solid epoxy resin, 0.1-0.3 parts of dispersant, 1-3 parts of anti-settling agent, 0.5-1 parts of thickener, 10-14 parts of resin diluent, 65-75 parts of anti-rust pigment, and 3-5 parts of organic solvent;
[0007] The weight proportions of the raw materials of component B are as follows: 40-50 parts of curing agent, 40-50 parts of curing diluent, and 0.5-3 parts of silane coupling agent;
[0008] The anti-rust pigment is a nano inorganic phosphate, a polypyrrole nano sheet, a zinc powder, a phosphorus iron powder, an aluminum tripolyphosphate, and a modified zinc phosphate in a mass ratio of 2-3:2-3:20-40:2-5:2-5:2-5.
[0009] Preferably, the general formula of the nanophosphate is LiMPO 4 , wherein M is one of Co, Ni, Mg, and Fe.
[0010] Preferably, the dispersant is a modified polyurethane polymer dispersant.
[0011] Preferably, the anti-settling agent is lithium-based bentonite, and the thickener is lithium-based montmorillonite.
[0012] Preferably, the resin diluent is a mixture of butyl glycidyl ether, ethylene glycol diglycidyl ether and butanediol glycidyl ether in a weight ratio of 1-2:3-8:3-8; the organic solvent is one or more of an alcohol solvent, an aromatic hydrocarbon solvent and a ketone solvent.
[0013] Preferably, the polypyrrole nanosheets are prepared by the following preparation method: pyrrole, polyvinyl pyrrolidone and sodium chloride are added to ethanol, heated and stirred until the ethanol is completely volatilized, and then an iron salt solution is added, heated and stirred to obtain polypyrrole nanosheets.
[0014] Preferably, the curing agent is a polyamide curing agent and a modified amine curing agent in a mass ratio of 2-3:1-2.
[0015] Preferably, the curing diluent is a mixture of xylene, isopropanol, propylene glycol methyl ether and dipropylene glycol methyl ether in a weight ratio of 1~2:1~2:0.5~1:0.5~1.
[0016] Preferably, the silane coupling agent is one of vinyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltrimethoxysilane, aminopropyltrihexyloxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
[0017] Another object of the present invention is to provide a method for preparing a salt spray resistant two-component epoxy zinc-rich primer, comprising the following steps:
[0018] The preparation of component A includes:
[0019] S1, mixing and stirring liquid epoxy resin, solid epoxy resin, dispersant, anti-settling agent, thickener, resin diluent, anti-rust pigment, and organic solvent, and grinding to obtain slurry;
[0020] S2, adding the anti-rust pigment to the slurry prepared in S1, mixing and stirring evenly, and then filtering to obtain component A;
[0021] The preparation of the component B comprises: mixing and stirring the raw materials for preparing the component B uniformly, and then filtering to obtain the component B;
[0022] The prepared component A and the prepared component B are mixed evenly according to a certain proportion to obtain an epoxy zinc-rich primer.
[0023] Another object of the present invention is to provide a coating film, which is formed by coating and curing the above-mentioned salt spray resistant two-component epoxy zinc-rich primer on the surface of a substrate.
[0024] Compared with the prior art, the advantages of the present invention are:
[0025] (1) The present invention uses polypyrrole with good electrical conductivity, especially flaky polymer nanosheets containing a large amount of doped iron salts. On the one hand, the amount of zinc powder in the zinc-rich coating is reduced, thereby avoiding excessive zinc content in the zinc-rich primer, which causes the zinc-rich coating to have reduced toughness and adhesion and porous coating; on the other hand, it can prevent oxidants from passing through the coating to reach the metal surface, making the underlying coating more dense, enhancing the corrosion resistance, and improving the salt spray resistance.
[0026] (2) The anti-settling agent of the present invention is lithium-based bentonite, and the thickener is lithium-based montmorillonite. The addition of the two has a synergistic effect, which can increase the viscosity of the primer and form a solvated film and a three-dimensional network structure on the surface of the base material particles to support and prevent the particles from sinking, thereby improving the density of the base coating. Even when the paint is applied thickly, it will not shrink in volume and crack.
[0027] (3) Nanophosphate has electrical conductivity and chemical stability. The present invention adds it to the primer to serve as an auxiliary anode for zinc. In addition, nanophosphate and polypyrrole nanosheets have a synergistic effect in the coating, enhancing the mechanical properties and corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The surface appearance of the paint film of the primer of Example 1 of the present invention and Comparative Examples 1-4 after the CASS test.
[0029] Wherein, (a) is a surface appearance diagram of the paint film of the primer of Example 1 of the present invention after the CASS test;
[0030] (b) is a surface appearance diagram of the paint film of the primer of comparative example 1 of the present invention after the CASS test;
[0031] (c) is a surface appearance diagram of the paint film of the primer of comparative example 2 of the present invention after CASS test;
[0032] (d) is a surface appearance diagram of the paint film of the primer of comparative example 3 of the present invention after the CASS test;
[0033] (e) is a surface appearance diagram of the paint film of the primer of comparative example 4 of the present invention after the CASS test. Implementation
[0034] The present invention is further described in detail below with reference to the embodiments.
[0035] A salt spray resistant two-component epoxy zinc-rich primer, comprising a component A and a component B in a weight ratio of 20:1.5;
[0036] The weight proportions of the raw materials in the A component are as follows: 10 parts of liquid epoxy resin (from Guodu Chemical Co., Ltd.), 13 parts of solid epoxy resin (from Guodu Chemical Co., Ltd.), 0.3 parts of EFKA4010 dispersant, 3 parts of lithium bentonite, 0.5 parts of lithium montmorillonite, 14 parts of resin diluent, 75 parts of anti-rust pigment, and 5 parts of n-butanol; wherein the resin diluent is a mixture of butyl glycidyl ether, ethylene glycol diglycidyl ether, and butanediol glycidyl ether in a weight ratio of 2:7:7, and the anti-rust pigment is nano-LiMgPO in a mass ratio of 3:3:35:5:3:5. 4 , polypyrrole nanosheets, zinc powder (spherical zinc powder with a specification of 500 mesh, an average particle size of 5-7μm, and a maximum particle size of ≤30μm), ferrophosphide powder (from Henan Yingchuan New Materials Co., Ltd.), aluminum tripolyphosphate (from Henan Yingchuan New Materials Co., Ltd.), and modified zinc phosphate (from Henan Yingchuan New Materials Co., Ltd.). The polypyrrole nanosheets were prepared by the following preparation method: 5.6g of pyrrole, 1.1g of polyvinylpyrrolidone, and 22g of sodium chloride were added to 60mL of ethanol, heated to 70°C and stirred for 60min until the ethanol was completely evaporated, and then 0.3g / mL of ferric chloride solution was added, heated to 80°C and stirred for 60min to obtain polypyrrole nanosheets.
[0037] The weight proportions of the raw materials of component B are as follows: 45 parts of curing agent, 48 parts of curing diluent, and 2 parts of OFS-6040 silane coupling agent; wherein the curing agent is a polyamide curing agent (351A, Air Chemicals, Inc., USA) and a modified amine curing agent (Ancamine 2422, Air Chemicals, Inc., USA) in a mass ratio of 2:1, and the curing diluent is a mixture of xylene, isopropyl alcohol, propylene glycol methyl ether, and dipropylene glycol methyl ether in a weight ratio of 2:2:1:1.
[0038] A method for preparing a salt spray resistant two-component epoxy zinc-rich primer comprises the following steps:
[0039] The preparation of component A includes:
[0040] S1. Fully stir the liquid epoxy resin, solid epoxy resin, dispersant, anti-settling agent, thickener, resin diluent, anti-rust pigment and organic solvent at a speed of 1500 r / min for 20 min to fully mix the raw materials to obtain a mixture, and then pump the mixture into a sand mill for grinding until the fineness is less than 100 μm to obtain a slurry;
[0041] S2, adding the anti-rust pigment to the slurry prepared in S1, stirring at a speed of 1000 r / min for 30 min, stirring evenly, and filtering through a 120-mesh filter to obtain component A;
[0042] The preparation of component B comprises: fully stirring the raw materials for preparing component B at a speed of 1200 r / min for 30 minutes, stirring evenly, and then filtering with a 120-mesh filter to obtain component B;
[0043] The prepared component A and the prepared component B are mixed evenly according to a certain proportion to obtain an epoxy zinc-rich primer. Example 2
[0044] A salt spray resistant two-component epoxy zinc-rich primer and a preparation method thereof, comprising component A and component B in a weight ratio of 18:1.2;
[0045] The weight proportions of the raw materials in the A component are as follows: 8 parts of liquid epoxy resin (from Guodu Chemical Co., Ltd.), 12 parts of solid epoxy resin (from Guodu Chemical Co., Ltd.), 0.2 parts of EFKA4010 dispersant, 2 parts of lithium bentonite, 1 part of lithium montmorillonite, 12 parts of resin diluent, 70 parts of anti-rust pigment, and 4 parts of n-butanol; wherein the resin diluent is a mixture of butyl glycidyl ether, ethylene glycol diglycidyl ether, and butanediol glycidyl ether in a weight ratio of 2:5:5, and the anti-rust pigment is nano-LiFePO4 in a mass ratio of 3:2:40:5:3:3. 4 , polypyrrole nanosheets, zinc powder (spherical zinc powder with a specification of 500 mesh, an average particle size of 5-7μm, and a maximum particle size of ≤30μm), ferrophosphide powder (from Henan Yingchuan New Materials Co., Ltd.), aluminum tripolyphosphate (from Henan Yingchuan New Materials Co., Ltd.), and modified zinc phosphate (from Henan Yingchuan New Materials Co., Ltd.). The polypyrrole nanosheets were prepared by the following preparation method: 5.6g of pyrrole, 1.1g of polyvinylpyrrolidone, and 22g of sodium chloride were added to 60mL of ethanol, heated to 70°C and stirred for 60min until the ethanol was completely evaporated, and then 0.3g / mL of ferric chloride solution was added, heated to 80°C and stirred for 60min to obtain polypyrrole nanosheets.
[0046] The weight proportions of the raw materials of component B are as follows: 50 parts of curing agent, 50 parts of curing diluent, and 2 parts of OFS-6040 silane coupling agent; wherein the curing agent is a polyamide curing agent (351A, Air Chemicals, Inc., USA) and a modified amine curing agent (Ancamine 2422, Air Chemicals, Inc., USA) in a mass ratio of 3:2, and the curing diluent is a mixture of xylene, isopropyl alcohol, propylene glycol methyl ether, and dipropylene glycol methyl ether in a weight ratio of 1:2:1:1.
[0047] A method for preparing a salt spray resistant two-component epoxy zinc-rich primer comprises the following steps:
[0048] The preparation of component A includes:
[0049] S1. Fully stir the liquid epoxy resin, solid epoxy resin, dispersant, anti-settling agent, thickener, resin diluent, anti-rust pigment and organic solvent at a speed of 1500 r / min for 20 min to fully mix the raw materials to obtain a mixture, and then pump the mixture into a sand mill for grinding until the fineness is less than 100 μm to obtain a slurry;
[0050] S2, adding the anti-rust pigment to the slurry prepared in S1, stirring at a speed of 1000 r / min for 30 min, stirring evenly, and filtering through a 120-mesh filter to obtain component A;
[0051] The preparation of component B comprises: fully stirring the raw materials for preparing component B at a speed of 1200 r / min for 30 minutes, stirring evenly, and then filtering with a 120-mesh filter to obtain component B;
[0052] The prepared component A and the prepared component B are mixed evenly according to a certain proportion to obtain an epoxy zinc-rich primer. Example 3
[0053] A salt spray resistant two-component epoxy zinc-rich primer and a preparation method thereof, comprising component A and component B in a weight ratio of 15:1;
[0054] The weight proportions of the raw materials in the A component are as follows: 7 parts of liquid epoxy resin (from Guodu Chemical Co., Ltd.), 10 parts of solid epoxy resin (from Guodu Chemical Co., Ltd.), 0.1 parts of EFKA4010 dispersant, 1 part of lithium bentonite, 0.5 parts of lithium montmorillonite, 12 parts of resin diluent, 65 parts of antirust pigment, and 3 parts of n-butanol; wherein the resin diluent is a mixture of butyl glycidyl ether, ethylene glycol diglycidyl ether, and butanediol glycidyl ether in a weight ratio of 1:8:8, and the antirust pigment is nano-LiCoPO in a mass ratio of 3:3:40:2:2:5. 44, polypyrrole nanosheets, zinc powder (spherical zinc powder with a specification of 500 mesh, an average particle size of 5-7μm, and a maximum particle size of ≤30μm), ferrophosphide powder (from Henan Yingchuan New Materials Co., Ltd.), aluminum tripolyphosphate (from Henan Yingchuan New Materials Co., Ltd.), and modified zinc phosphate (from Henan Yingchuan New Materials Co., Ltd.). The polypyrrole nanosheets were prepared by the following preparation method: 5.6g of pyrrole, 1.1g of polyvinylpyrrolidone, and 22g of sodium chloride were added to 60mL of ethanol, heated to 70°C and stirred for 60min until the ethanol was completely evaporated, and then 0.3g / mL of ferric chloride solution was added, heated to 80°C and stirred for 60min to obtain polypyrrole nanosheets.
[0055] The weight proportions of the raw materials of component B are as follows: 40 parts of curing agent, 50 parts of curing diluent, and 2 parts of OFS-6040 silane coupling agent; wherein the curing agent is a polyamide curing agent (351A, Air Chemicals, Inc., USA) and a modified amine curing agent (Ancamine 2422, Air Chemicals, Inc., USA) in a mass ratio of 3:2, and the curing diluent is a mixture of xylene, isopropyl alcohol, propylene glycol methyl ether, and dipropylene glycol methyl ether in a weight ratio of 1:1:1:1.
[0056] A method for preparing a salt spray resistant two-component epoxy zinc-rich primer comprises the following steps:
[0057] The preparation of component A includes:
[0058] S1. Fully stir the liquid epoxy resin, solid epoxy resin, dispersant, anti-settling agent, thickener, resin diluent, anti-rust pigment and organic solvent at a speed of 1500 r / min for 20 min to fully mix the raw materials to obtain a mixture, and then pump the mixture into a sand mill for grinding until the fineness is less than 100 μm to obtain a slurry;
[0059] S2, adding the anti-rust pigment to the slurry prepared in S1, stirring at a speed of 1000 r / min for 30 min, stirring evenly, and filtering through a 120-mesh filter to obtain component A;
[0060] The preparation of component B comprises: fully stirring the raw materials for preparing component B at a speed of 1200 r / min for 30 minutes, stirring evenly, and then filtering with a 120-mesh filter to obtain component B;
[0061] The prepared component A and the prepared component B are mixed evenly according to a certain proportion to obtain an epoxy zinc-rich primer.
[0062] Comparative Example 1
[0063] Compared with Example 1, the only difference is that no nano-phosphate is added.
[0064] Comparative Example 2
[0065] Compared with Example 1, the only difference is that no polypyrrole nanosheets are added.
[0066] Comparative Example 3
[0067] Compared with Example 1, the only difference is that no lithium-based bentonite is added.
[0068] Comparative Example 4
[0069] Compared with Example 1, the only difference is that no lithium-based montmorillonite is added.
[0070] Performance Test:
[0071] The epoxy zinc-rich primer prepared in Example 1 and Comparative Examples 1-4 was applied to the surface of the tinplate by brushing, and dried at room temperature. The thickness of the coating film was 30±3 μm. According to GB / T 10125 Artificial Atmosphere Corrosion Test, a CASS test (copper salt accelerated acetate spray test) was carried out at 50°C±2°C for 96 hours to observe whether there were defects on the surface of the paint film. The surface appearance of the paint film of Example 1 was basically unchanged, while the surface of the paint film of Comparative Examples 1-4 had small bubbles, spots, and shedding. For details, see Figure 1 .
[0072] The epoxy zinc-rich primer prepared in Examples 1-3 and Comparative Examples 1-4 was applied to the surface of the tinplate by brushing, dried at room temperature, and the thickness of the coating was 20±3 μm. According to the provisions of GB / T3668-2009 Zinc-rich Primer, performance tests were carried out respectively, and the results are shown in Table 1.
[0073] Each performance test method is carried out according to the following standards:
[0074] Adhesion is tested according to GB5210-2006 "Adhesion test of paint and varnish by pull-off method";
[0075] Flexibility is measured according to GB1731-1993 "Determination of paint film flexibility";
[0076] Impact resistance is carried out according to GB / T1732-1993 "Impact resistance of paint film";
[0077] The salt spray resistance is carried out according to GB1771-2007 “Determination of neutral salt spray resistance of paints and varnishes”.
[0078] Table 1
[0079]
[0080] The epoxy zinc-rich primer prepared in Examples 1-3 and Comparative Examples 1-4 was applied to the surface of the corroded hot-rolled plate substrate by brushing, and dried at room temperature. The thickness of the coating film was 90±10 μm. According to the provisions of GB / T3668-2009 Zinc-rich Primer, performance tests were carried out respectively, and the results are shown in Table 2.
[0081] Each performance test is carried out in the following manner:
[0082] Adhesion is tested in accordance with GB9268-1998 "Scratching test for paint and varnish films";
[0083] The salt spray resistance is carried out in accordance with GB1771-2007 "Determination of neutral salt spray resistance of paints and varnishes".
[0084] Table 2
[0085]
[0086] In addition to the above embodiments, the present invention also includes other implementation modes. Any technical solutions formed by equivalent transformation or equivalent replacement should fall within the protection scope of the claims of the present invention.
Claims
1. A salt spray resistant two-component epoxy zinc-rich primer, characterized in that: It includes component A and component B in a weight ratio of (15-20):(1-1.5); The weight proportions of the raw materials in the A component are as follows: 7-10 parts of liquid epoxy resin, 10-15 parts of solid epoxy resin, 0.1-0.3 parts of dispersant, 1-3 parts of anti-settling agent, 0.5-1 parts of thickener, 10-14 parts of resin diluent, 65-75 parts of anti-rust pigment, and 3-5 parts of organic solvent; The weight proportions of the raw materials of component B are as follows: 40-50 parts of curing agent, 40-50 parts of curing diluent, and 0.5-3 parts of silane coupling agent; Wherein, the anti-rust pigment is a nano inorganic phosphate, polypyrrole nanosheets, zinc powder, ferrophosphorus powder, aluminum tripolyphosphate, and modified zinc phosphate in a mass ratio of 2-3:2-3:20-40:2-5:2-5:2-5; The anti-settling agent is lithium-based bentonite, and the thickener is lithium-based montmorillonite; The polypyrrole nanosheets are prepared by the following preparation method: pyrrole, polyvinyl pyrrolidone and sodium chloride are added to ethanol, heated and stirred until the ethanol is completely volatilized, and then an iron salt solution is added, heated and stirred to obtain polypyrrole nanosheets; The general formula of the nano inorganic phosphate is LiMPO4, wherein M is one of Co, Ni, Mg and Fe.
2. The salt spray resistant two-component epoxy zinc-rich primer according to claim 1, characterized in that: The resin diluent is a mixture of butyl glycidyl ether, ethylene glycol diglycidyl ether and butanediol glycidyl ether in a weight ratio of 1-2:3-8:3-8; the organic solvent is one or more of an alcohol solvent, an aromatic hydrocarbon solvent and a ketone solvent.
3. The salt spray resistant two-component epoxy zinc-rich primer according to claim 1, characterized in that: The curing agent is a polyamide curing agent and a modified amine curing agent in a mass ratio of 2-3:1-2.
4. The salt spray resistant two-component epoxy zinc-rich primer according to claim 1, characterized in that: The curing diluent is a mixture of xylene, isopropanol, propylene glycol methyl ether and dipropylene glycol methyl ether in a weight ratio of 1-2:1-2:0.5-1:0.5-1.
5. The salt spray resistant two-component epoxy zinc-rich primer according to claim 1, characterized in that: The silane coupling agent is one of vinyl trimethoxy silane, vinyl triethoxy silane, γ-aminopropyl trimethoxy silane, 3-aminopropyl triethoxy silane, and γ-methacryloxypropyl trimethoxy silane.
6. A method for preparing a salt spray resistant two-component epoxy zinc-rich primer according to any one of claims 1 to 5, characterized in that: The following steps are involved: The preparation of component A includes: S1, mixing and stirring liquid epoxy resin, solid epoxy resin, dispersant, anti-settling agent, thickener, resin diluent, anti-rust pigment, and organic solvent, and grinding to obtain slurry; S2, adding the anti-rust pigment to the slurry prepared in S1, mixing and stirring evenly, and then filtering to obtain component A; The preparation of the component B comprises: mixing and stirring the raw materials for preparing the component B uniformly, and then filtering to obtain the component B; The prepared component A and the prepared component B are mixed evenly according to a certain proportion to obtain an epoxy zinc-rich primer.
7. A coating film, characterized in that: The coating film is formed by coating and curing the salt-spray resistant two-component epoxy zinc-rich primer described in any one of claims 1 to 5 on the surface of the substrate.
Citation Information
Patent Citations
High-solid surface-tolerant epoxy zinc-rich primer and preparation method and application thereof
CN110144160A
Gray modified composite ferrotitanium powder anti-rust pigment and preparation method thereof
CN110256885A
Anticorrosive conductive coating and preparation method thereof
CN114525051A